MODELLING OF SAPROPEL FLOW (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 1999)
The most important problem for sapropel extraction by means of pumping systems is the reduction of energy costs for the transportation ofpure humidity sapropel in pipelines. The main parameters, which create energy losses in the flow, are: plastic viscosity pp and boundary shearing stress r0. The article presents results of mathematical modelling of pure sapropel flow. An equation is worked out which describes changes of shear stress in dependence of shear rate in the pure sapropel flow. The equation can be used for modelling different non-Newtonian plastic fluids with non? linear flow curves. The equation gives good accordance between theory and results of the experiment. Coefficient of determination reaches value R2-0.92-0.98The equation worked out for calculating of sapropel flow gives good accordance with experiment, R2=0.97. It can be used for calculating of non-Newtonian flows.